ANALISIS PERBANDINGAN BIAYA DAN WAKTU FLEXIBLE PAVEMENT DENGAN CAKAR AYAM MODIFIKASI PADA JALAN SEKAR PUTIH KOTA MOJOKERTO (Jurnal Spesialis Teknik Sipil (JSpTS), 2023)
Mojokerto is the main supporting city for the capital of East Java Province. The city is experiencing very rapid development as seen from the local revenue which has increased every year. The city of Mojokerto is one of the areas included in the Surabaya metropolitan area, namely Gerbangkertosusila. Currently, there is the Surabaya - Mojokerto Toll Road, which is often called the SUMO Toll Road. As is the case with Sekar Putih Street in Mojokerto City, this road is an alternative road that connects the Mojokerto city area with Mojokerto district if there is congestion in the Mojokerto city area, especially the Mojokerto bay pass road, then this route will be used as an alternative road with heavy vehicles passing by on this road. But the problem is that Jalan Sekar Putih has poor soil carrying capacity, so the road is often damaged and bleeds quickly, so the city government often has to carry out repairs/maintenance on Jalan Sekar Putih. So it is necessary to do a study by comparing the types of construction that are efficient with the Velue Engineering Method between Flexible Pavement structures and Modified Chicken Claws (results from VE) which are used to solve problems on the Sekarputih road in Mojokerto City.The results of the analysis of cost requirements and their maintenance costs are more efficient. Modified Chicken Claws and time for the construction of the Modified Chicken Claw system are 11.11% more efficient than Flexible Pavement construction.written in Indonesian and English with the following qualifications: 1 paragraph, spaced 1, font size 11 pt, Cambria 250 – 300 words. Abstract contains the background of the research, objectives, research methods, conclusions and contributions of researchers in scientific field.